Manajemen Media Center Masjid Raya Bandung Dalam Mempublikasikan Kegiatan Keagamaan Melalui Media Sosial - Rubiyatul Sadiyah; Komaruddin Shaleh; Muhammad Fauzi Arif (UNISBA Press, 2024)
Abstract. The publication of religious activities through social media has become a common thing done by large mosques in this era, one of which is the Grand Mosque of Bandung. The Media Center of the Bandung Grand Mosque has the responsibility of managing social media, one of which is Instagram on the @official.masjidrayabandung which is used in preaching and disseminating information on religious activities held by the Bandung Grand Mosque. The problem in this research is that there is no consistency in publications carried out by the media center of the Grand Mosque of Bandung on social media. This research aims to obtain data on media center management in publicizing religious activities through social media. This type of research is qualitative with a descriptive-analytical method. Data collection through observation, interviews, and documentation. The results of this research show that the media center publishes religious activities through social media using four stages in management such as Planning, namely compiling informative content and in accordance with the schedule of religious activities in the mosque, Organizing steps for the division of duties and responsibilities that are clearly defined, Actuating using Instagram social media in publicizing religious activities and collaborating with external parties, Controlling conducting supervision and evaluation. Supervision is carried out periodically directly through social media. Meanwhile, the evaluation is carried out after the activity and is carried out again during the formulation of programs at the deliberations of the management work meeting. Abstrak. Publikasi kegiatan keagamaan melalui media sosial sudah menjadi hal yang lumrah dilakukan oleh masjid-masjid besar di zaman ini, salah satunya adalah Masjid Raya Bandung. Media Center Masjid Raya Bandung memiliki tanggungjawab dalam mengelola media sosial salah satunya Instagram pada @official.masjidrayabandung yang digunakan dalam berdakwah dan menyebarkan informasi kegiatan keagamaan yang diadakan oleh Masjid Raya Bandung. Permasalahan pada penelitian ini adalah belum ada konsistensi publikasi yang dilakukan oleh media center Masjid Raya Bandung di media sosial. Penelitian ini bertujuan untuk memperoleh data tentang manajemen media center dalam mempublikasikan kegiatan keagamaan melalui media sosial. Jenis penelitian ini kualitatif dengan metode deskriptif-analisis. Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa media center mempublikasikan kegiatan keagamaan melalui media sosial menggunakan empat tahap dalam manajemen seperti Planning Planning (Perencanaan) yaitu menyusun konten yang informatif dan sesuai dengan jadwal kegiatan keagamaan di masjid, Organizing (Pengorganisasian) langkah pembagian tugas dan tanggung jawab yang ditetapkan dengan jelas, Actuating (Pelaksanaan) menggunakan media sosial instagram dalam mempublikasikan kegiatan keagamaan dan berkolaborasi dengan pihak luar, Controlling (Pengawasan) melakukan pengawasan dan evaluasi. Pengawasan dilakukan secara berkala langsung melalui media sosial. Sedangkan evaluasi dilakukan setelah kegiatan dan dilakukan kembali saat perumusan program-program pada musyawaran rapat kerja pengurus.